What makes the re-instatement of night watchmanship dubious in Turkey: myth making, identity crisis and securitization policies. (1st January 2023) - Demirtaş-Milz, Neslihan; Barbak, Ahmet
ABSTRACT : Turkey's institution of night watchmanship, or bekçilik, almost vanished during the 1990s as new recruitment was halted. Since 2016, however, the ruling Justice and Development Party (AKP) has renewed recruitment in line with its agenda of revitalizing the institution, with recruits now officially named Market and Neighborhood Watchmen. The new regulatory and administrative context is highly centralized while their duties are scarcely different from those of the regular police forces, giving the institution's longstanding ambiguity or in-betweenness a more complicated form. In its attempt to publicly legitimize the institution, the AKP has relied on myth creation. Accordingly, this article contextualizes this process of double myth creation at the intersection of Turkey's neoliberal security sector reforms and AKP's securitization policies. In doing so, the article reveals the reasons underlying growing public anxiety regarding the institution.